Utilizing Deep Reinforcement Learning, EGO-Swarm Parameter Control determines the path of the drone - Conrad Bombongan; Tanda Selamat; Johan Johan; Waisen Waisen (Jurnal Minfo Polgan, 2024)
The recent attention garnered by the EGO-Swarm system is due to its successful generation of smooth drone flight paths in complex real-world environments. Among the various parameter values utilized by EGO-Swarm for path generation, the maximum speed and maximum acceleration of the drone play a critical role in enhancing flight performance. However, in the current EGO-Swarm setup, these parameter values remain fixed during path creation, despite the potential need for real-time adjustments in dynamic environments. Therefore, there is a need to dynamically adapt these values to the evolving real-time environment. This paper proposes a novel algorithm that dynamically adjusts the maximum speed and maximum acceleration using hierarchical deep reinforcement learning in response to real-time environmental changes. To assess the effectiveness of the proposed method, a comparative experiment is conducted between the existing EGO-Swarm algorithm and the proposed algorithm in a ROS simulation. The experimental results reveal that the proposed algorithm surpasses the existing EGO-Swarm algorithm in terms of average speed improvement and path length.(Zhou et al., 2021)